The underrepresentation of women in sport leadership in South Africa - Adom-Aboagye, Nana Akua Achiaa; Burnett, Cora (Frontiers in Sports and Active Living, 2023)
The lack of representation of women in sport leadership, despite global movements and policies that have found some traction, is a persistent, unremitting challenge globally, and especially in South Africa. This study aimed to explore the intersections of gender and sports ideology and its impact on gender (in)equity in the South African context. The study draws on African feminist theories and perspectives as a conceptual framework. Twenty-eight interviews with prominent administrators, gender activists in sport, and practitioners from the sport-for-development sector and thematic document analysis provided qualitative data for the generation of three main themes relating to: (i) norms and values; (ii) male resistance; and (iii) agency. The results of the study show minimal traction on changing patriarchally informed cultural beliefs towards women with men as gatekeepers and masculinity framed for leadership attributes in most sports. Within an African feminist viewpoint, gender justice is multilayered and the inclusion of women within a holistic environment of shared decision-making and equitable resource mobilisation and distribution cannot be achieved through advocacy alone but necessitate the mainstreaming of a gender agenda to meaningfully address transformative change of sport systems and practices.